Advances in hadrontherapy dosimetry. (September 2016) - Raffaele, L.
Abstract : This paper investigates suitability of two new commercial solid-state detectors as alternative to reference detectors for dosimetry of proton and carbon ion beams, as for scattered and scanned beams. Investigated detectors are PTW microDiamond and PTW PR 60020 diode that have very small measuring volume with extremely reduced thickness of active detector layer (1 μ m for diamond, 20 μ m for diode). Both detectors were tested in 62 MeV ocular proton therapy beam (INFN-LNS), PTW microdiamond was tested in clinical scanned carbon ion beams up to 400 MeV/u (CNAO), PTW PR 60020 Dosimetry was tested in scanned proton beams up to 250 MeV (CNAO). As for scattered and scanned proton and carbon ion beams, both detectors showed excellent short-term precision (<0.5%), a good linear behavior with dose ( R 2 = 1) and dose rate independence ( ⩽ 1%) in the investigated irradiation conditions. Negligible differences were observed in depth-dose distributions measured by investigated detectors and reference plane-parallel Markus chamber, as for unmodulated and modulated beams, both for scattered and scanned fields. Values of Peak-to-Plateau ratios for unmodulated beams measured by tested detectors and Markus Chamber agree to ± 2% as for protons and carbon ions, indicating that investigated solid-state detectors are not affected by the LET values. Moreover microDiamond and diode measure with great accuracy basic parameters of modulated clinical proton beams: (i) range (d'90) (ii) SOBP length (m'90) (iii) distal-dose falloff (80–20%). Diode "edge-on" arrangement of PTW diode provides lateral beam profiles with a spatial resolution comparable to EBT3 film also for narrow proton beams of ocular proton therapy. Furthermore, PTW diode is suitable for determining OFs of narrow proton beams in ocular protontherapy up to collimator 5 mm in diameter, as resulted by an intercomparison with radiochromic EBT3 films.